Inequalities in total fertility rate in Sierra Leone, 2008–2019 - Augustus Osborne; Umaru Sesay; Mohamed S. Bah; Camilla Bangura; Bright Opoku Ahinkorah (BMC Public Health)
Abstract Background Total fertility rate measures the average number of children a woman is expected to have during her reproductive age (typically 15-49 years). Despite the national decline in Sierra Leone, significant disparities in total fertility rates persist across socioeconomic and geographic lines. This study investigated the inequalities in total fertility rate among women in Sierra Leone between 2008 and 2019. Methods We utilized data from the three rounds of the Sierra Leone Demographic Health Survey conducted in 2008, 2013, and 2019. The World Health Organization’s Health Equity Assessment Toolkit was employed to calculate various inequality measures, including simple difference, ratio, population attributable risk, and population attributable fraction. The assessment focused on inequality across four stratifiers: economic status, level of education, place of residence, and sub-national province. Results The total fertility rate declined in Sierra Leone throughout the period, dropping from 5.0 births per woman in 2008 to 4.3 births per woman in 2019. Economic disparity among women in the richest quintile compared with those in the poorest quintile increased from 3.0 births per woman in 2008 to 3.1 births per woman in 2019. The ratio between women in the richest quintile compared with those in the poorest quintile also increased from 1.9 in 2008 to 2.1 in 2019; the confidence interval suggest inequality, with women in the poorest quintile disproportionately affected. Inequality in education among women with secondary education or higher compared with those with no education decreased from 2.7 births per woman in 2008 to 1.9 births per woman in 2019. The ratio between women with secondary education or higher compared with those with no education decreased from 1.9 in 2008 to 1.6 in 2019, and the confidence interval suggest an inequality with women with no education disporportionately affected. Provincial inequality among women who resided in Western area compared with those in Eastern province decreased slightly from 2.3 births per woman in 2008 to 2.2 births per woman in 2019. The ratio between women who resided in Western province compared with those in Eastern province increased from 1.6 in 2008 to 1.7 in 2019 and indicate an inequality among women in the provinces. Conclusion The results indicate substantial socioeconomic and geographical disparities in total fertility rate among women in Sierra Leone that require targeted policy interventions. The persistent and widening economic gap between women in the richest and poorest quintiles suggests that poverty reduction strategies and economic empowerment programs for low-income women need strengthening. While the decreasing educational inequality is encouraging, the continued disadvantage faced by women with no education indicates a need for enhanced educational access and adult literacy programs. The provincial disparities between Western and Eastern provinces point to a need for balanced provincial development policies and improved resource distribution, particularly in the Eastern province, where women face greater disadvantages. These implications collectively suggest that policymakers should adopt an integrated approach that combines economic empowerment, educational initiatives, and provincial development strategies to address these intersecting inequalities in TFR effectively.